FEATURES OF EXOGENIC DEVELOPMENT OF TRICHURISES SEPARATED FROM DOMESTIC GOATS (CAPRA HIRCUS LINNAEUS, 1758) - Prijma, O. B.; Stybel, V. V.; Mazur, I. Ya. (Scientific Progress & Innovations, 2019)
In many countries of the world, goat farming is an important traditional and strategic industry of the economy due to its poly-productivity. This industry provides the population with the most valuable food – milk and meat, and the processing industry − with raw materials. It also contributes to the intensive use of land resources and the formation of food security for the population of Ukraine on the basis of creating the necessary state reserves of livestock farming products. The researches were performed in the laboratory of the Department of Parasitology and Ichthyopathology, Stepan Gzhytskyj Lviv National University of Veterinary Medicine and Biotechnologies. The eggs of Trichuris ovis were isolated from the gonads of female trichurises, the collection of which was performed by the method of complete helminthological dissection of the large intestine of dead or forced slaughtered goats. According to the research results, it has been established that eggs of T. ovis goat nematodes under laboratory conditions regardless of the temperature regime undergo 7 stages of embryogenesis: protoplast, formation of two blastomeres, formation of three or more blastomeres, bean-shaped embryo, tadpoles, larval formation, and formation of a moving larva. It has been proved that the time of egg developments to invasive stage and the degree of their viability depends on the cultivation temperature. The most optimal mode for the development of T. ovis eggs in vitro was the temperature of 20 °C, at which their viability was 85.33±1.53 %. In this case, the stop in the development and death were observed in 14.67±1.53 % of trichuris eggs of this species. At 24 °C and 28 °C temperatures, the number of eggs with culture invasive larvae decreased and amounted to 83.33±1.20 and 78.33±2.03 %. The development of 16.67±1.20 and 21.67±2.03 % of eggs stopped, respectively. At the same time, with increasing the temperature control, the terms of embryogenesis completion decreased. At a temperature of 20 °C the development was ended in 39 days and was the longest. At a temperature of 24 °C, the formation of invasive eggs occurred within 30 days, and at a temperature of 28 °C – within 27 days. Depending on the temperature factor, the protoplast stage occurred within 1–18 days, the formation of two blastomeres – 3–18 days, three or more blastomeres – 3–21 days, bean-shaped embryo − 6–30 days, tadpoles – 12–33 days, larvae formation – 15–36 days, moving larvae formation – 18–39 days.